(3QSGdI aj GdeLGR HeQJHI hGdeLGR HeQJHJjfs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hHYO aEfc SCdJ Yf eYfi bhdge GdeLGR HeQJHI hGdeLGR HeQJHJjf hCQOJ TQM Pdc hHjGfg s
(3BNQgG (B:s
(3GdeSJYGQ dg HNUhUg dYdGbI GdEWdGb hGdJbjjO aGage gPg GdMceI aEfgG VGdI GdeDef hcJH HChGNQ QHjY GdfHhi YGe (B1278 s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs